The Impacts of Constitutional Court Decisions on Criminal Policy of Indonesia: Implikasi Putusan Mahkamah Konstitusi Terhadap Politik Kriminal Indonesia - Akbar, Muhammad Fatahillah (Jurnal Konstitusi, 2024)
In substantive criminal law, the Constitutional Court (MK) has consistently acted as a negative legislature and not as a criminal policy maker. However, in procedural criminal law, the MK has taken on the role of a criminal policy maker. This article aims to examine the impact of the Constitutional Court’s decisions in judicial reviews on the development of criminal policy in Indonesia and to provide recommendations on how the MK should review criminal law in the future. This research is conducted using a doctrinal method strengthened by a statute and case approach. The findings show that, in substantive criminal law, the MK has only issued decisions for the decriminalization of offenses regulated by law, such as in the judicial review of the article on Defamation of the President and Unpleasant Acts in the Criminal Code (KUHP). However, in procedural criminal law, the MK has acted as a positive legislature, for example, by expanding pre-trial competences through its decisions. The MK has not been consistent in applying either judicial activism or judicial restraint in reviewing laws. In criminal policy, the MK should act as a negative legislature and be limited to decriminalization, as a form of judicial restraint.